ANALISIS OUTPUT ENERGI PEMBAKARAN CAMPURAN PREMIXED BUTANA-UDARA PADA MESO SCALE COMBUSTOR DENGAN SUDDEN EXPANSION DAN PLATE HOLDER SEBAGAI FLAME HOLDER - Hafidh Risvie Ardhian (STATOR: Jurnal Ilmiah Teknik Mesin, 2022)
Mesoscale combustor is a form of technology development that uses fossil fuel as its raw source of energy. This combustion has a potential to produce thermal energy that can be utilized as a source for micro-scale electricity generation or called a Micro Power Generator (MPG). The study was performed by observing the effect of variations on the combustor outlet diameter with the addition of sudden expansion and plate as flame holder on the meso scale combustor to the amount of heat energy produced experimentally. This research was done to the two outlet diameter variations, namely 8 mm, 10 mm. The results of the study showed that at the equivalent ratio condition (Ф) = 1, the combustor with an outlet diameter of 10 mm produced the highest total energy output and efficiency in the amount of 325.46 Watt and 9,77% respectively.